2008
DOI: 10.1002/jsfa.3202
|View full text |Cite
|
Sign up to set email alerts
|

Impact of goat milk powdered formulations on mineral absorption, peak bone mass and bone loss due to ovariectomy in rats

Abstract: BACKGROUND: Goat milk is recognised as nutritious, with benefits to growth and skeletal development. The initial aim of this study was to investigate the effect of three different goat milk formulae -a whole milk, a skim milk and a goat milk growing-up formula fortified with pre-and probiotics (Formula 1) -on mineral absorption and retention in rats. The effect of long-term intake of the fortified formula diet on peak bone mass and post-ovariectomy bone loss in rats was then investigated in a follow-up study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…3). Kruger et al [44] showed that the rats fed the fortified diet had a higher peak bone mass, bone mineral content, and density of the lumbar spine that may be due to fortified milk formulations' improved calcium and phosphorus absorption and retention. Bonjour et al [45] pointed out that consumption of yogurts fortified Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3). Kruger et al [44] showed that the rats fed the fortified diet had a higher peak bone mass, bone mineral content, and density of the lumbar spine that may be due to fortified milk formulations' improved calcium and phosphorus absorption and retention. Bonjour et al [45] pointed out that consumption of yogurts fortified Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Diet 6, containing the highest levels of vegetable oils, had the lowest levels of calcium absorption in the study. Kruger et al 4 using the same mix of vegetable oils found that the diet containing whole goat milk had significantly greater absorption of calcium than the diet containing goat skim milk powder and vegetable oils. They theorized, as did López Aliaga et al ,13 that this is in part due to a higher percentage of the more readily absorbed medium‐chain fatty acids found in goat milk.…”
Section: Discussionmentioning
confidence: 99%
“…The goat milk protein consisted of three different ratios of 20:80 (diets 1 and 4), 43:57 (diets 2 and 5) or 83:17 (diets 3 and 6) whey:casein. Diets 1–3 had milk fat, whereas diets 4–6 contained a mixture of palm, coconut and soybean oil in proportions used in previous work at this institute calculated to provide a similar fatty acid profile to milk fat 4. All diets had 10 g kg −1 corn oil to prevent essential fatty acid (EFA) deficiency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Kruger et al. () considered the effect of milk fatty acids and identified that the presence of goat milk lipids in the diet significantly increased the Ca and P content in the body of male rats, from 1.60% to 1.67% and 0.97% to 1.01%, respectively, when compared with control animals after 3 wk of feeding.…”
Section: Minerals Present In Milk and Dairy Productsmentioning
confidence: 99%